Legal Liability of Islamic Boarding School Administrators for Negligence in Building Construction Development: Pertanggungjawaban Hukum Pengelola Pondok Pesantren atas Kelalaian dalam Pembangunan Gedung - Ayu Wulandari, Deby; Sulaksono, Agam; Heru Romadhon, Ahmad (Fakultas Hukum Universitas Jambi, 2026)
Negligence in the construction of Islamic boarding school buildings may result in building failures that cause material losses and loss of life. This issue highlights the importance of compliance with administrative requirements and technical construction standards as legal instruments for safeguarding building occupants. This study aims to analyze the forms of negligence committed by Islamic boarding school administrators in building construction, the legal liabilities arising from such negligence, and the role of government oversight in supervising the development of educational facilities and infrastructure within Islamic boarding schools. This research employs a normative legal method using statutory and conceptual approaches. Legal materials are analyzed qualitatively through the interpretation of legislation, legal doctrines, and the case of the collapse of the Al-Khoziny Islamic Boarding School building in Sidoarjo Regency. The findings reveal that the negligence of Islamic boarding school administrators may take the form of administrative negligence due to failure to obtain building construction approval and technical negligence through the disregard of construction standards, planning requirements, supervisory mechanisms, and the involvement of qualified professionals. Such negligence gives rise to administrative, civil, and criminal liability for foundation administrators as the parties responsible for management and decision-making functions. The study further finds that the regulatory framework governing the supervision of Islamic boarding school construction has not established a clear mechanism for technical oversight, resulting in government supervision being predominantly reactive rather than preventive. The novelty of this study lies in the formulation of a legal liability model for Islamic boarding school administrators that integrates construction compliance obligations with strengthened preventive governmental oversight of building development to ensure occupant safety and legal certainty.